Desenvolvimento de células solares : influência do processo de formação do campo retrodifusor com pasta de alumínio - Gonçalves, Vanessa Alves (2013)
The goal of this work was to develop solar cells with aluminum back surface field by using the aluminum paste PV 381. Specifically, the influence of the metallization process on the rear was evaluated, the firing temperature of the metallization pastes and diffusion of Al was experimentally optimized, solar cells with phosphorus diffusied on the front face and on both sides were compared, the effect of passivation in the region of the back surface field and the surface density of the Al paste deposited on the back surface field were evaluated. Cells processed with phosphorus diffusion on both sides and rear metallization with busbars deposited before the deposition of the paste Al on all surface with exception of the regions with the busbars presented the best results. The best cell with an efficiency of 13.6 % was processed with temperature for drying the paste of Ag and Al of 300 ° C and 270 ° C respectively. The belt speed during the firing of the pastes affects slightly the efficiency of the devices. The initial minority carrier lifetime increased of 30 μs to 120 μs, after diffusion of phosphorus and remained at the value of about 200 μs after drying and firing the three metallization pastes. For solar cells with only diffusion of phosphorus on the front face, the silicon dioxide passivation on rear face reduced the efficiency. The best average efficiency of 15 % was obtained with aluminum diffusion/firing at 840 °C and 870 °C in devices with two layers of Al paste. Electrical parameters of the best solar cell were: Voc = 592 mV, Jsc = 33.5 mA/cm2, FF = 0.76 and efficiency of the 15.1 %. In this case, the average minority carrier diffusion length was of 1280 μm.